Surface properties of calcium carbonate modified with silica by sol-gel method - Pedrosa, Jorge (2016)
The physico chemical surface properties of precipitated calcium carbonate (PCC) modified with silica by sol-gel method were evaluated using inverse gas chromatography and compared to those of the original PCC. The modification of the surface of PCC crystals by a dense film of silica provided a slight decrease of the dispersive component of the surface energy and a significant decrease of the specific component of the work of adhesion with trichloromethane (a Lewis acidic probe). In addition, interactions measured with weak Lewis bases (1-alkenes) also revealed differences between PCC and PCC-silica samples. Differences in the surface properties (namely of the Lewis acid-base ones) of PCCs modified with distinct silica content (ca. 22 and 30 wt%), were also found, and were interpreted as being due to the different accessibility of silanol groups (Si-OH) on the materials surface: a higher prevalence of these acidic groups in the material with lower silica content increases the specific affinity to Lewis basic probes and decreases the affinity to Lewis acidic probe. X-ray photoelectron spectroscopy results confirmed the presence of silica on PCC, with a higher Si/Ca atomic ratio being found for the material with higher silica content.